2004
DOI: 10.1007/s10237-004-0041-z
|View full text |Cite
|
Sign up to set email alerts
|

TGF-?1, TGF-?3, and PGE2 regulate contraction of human patellar tendon fibroblasts

Abstract: To understand the role of tendon fibroblast contraction in tendon healing, we investigated the contraction of human patellar tendon fibroblasts (HPTFs) and its regulation by transforming growth factor-beta1 (TGF-beta1), TGF-beta3, and prostaglandin E(2) (PGE(2)). HPTFs were found to wrinkle the underlying thin silicone membranes, demonstrating that these tendon fibroblasts are contractile. Using fibroblast populated collagen gels (FPCGs), exogenous addition of TGF-beta1 or TGF-beta3 was found to increase fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 31 publications
(38 reference statements)
2
31
0
Order By: Relevance
“…It was found that tendon and skin fibroblasts exhibited different patterns of contraction, where tendon fibroblasts produced a lower maximum contraction force than skin fibroblasts (Eastwood et al, 1996). Recent studies from our laboratory demonstrated that HPTFs in collagen gels produced an average contraction of 0.2 nN/cell , and that TGF-b1 and TGF-b3 differentially regulated the tendon fibroblast contraction (Campbell et al, 2004).…”
Section: The Role Of Fibroblast Contraction In Tissue Healingmentioning
confidence: 97%
“…It was found that tendon and skin fibroblasts exhibited different patterns of contraction, where tendon fibroblasts produced a lower maximum contraction force than skin fibroblasts (Eastwood et al, 1996). Recent studies from our laboratory demonstrated that HPTFs in collagen gels produced an average contraction of 0.2 nN/cell , and that TGF-b1 and TGF-b3 differentially regulated the tendon fibroblast contraction (Campbell et al, 2004).…”
Section: The Role Of Fibroblast Contraction In Tissue Healingmentioning
confidence: 97%
“…Additionally, recent studies have found that TGF-β1 and TGF-β3, two isoforms of TGF-β, induce differential α-SMA expression and myofibroblast traction force. For instance, TGF-β1 induces higher α-SMA expression and traction force than TGF-β3 in human patellar tendon fibroblasts (Campbell et al 2004). On the other hand, soluble factors such as bFGF, PGE 2 , and γ -interferon inhibit TGF-β1-upregulated α-SMA expression and thus likely cause the downregulation of CTF (Burgess et al 2005;Hjelmeland et al 2004;Kawai-Kowase et al 2004;Kolodsick et al 2003).…”
Section: Cell Traction Forcementioning
confidence: 98%
“…43,44 Transforming growth factor-␤ also serves to regulate the synthesis of collagen in tendon mechanically during physical exercise. 45 During the initial repair process and the inflammatory phase, upregulation of growth factors and cytokines such as insulin-like growth factor-1 (IGF-1) stimulate the migration and proliferation of fibroblasts and inflammatory cells to the wound site.…”
Section: Molecular Mechanismsmentioning
confidence: 99%